A Thousand Splendid Suns - Khaled Hosseini
- An Afghani `War And Peace' That Promises To Be One of 2007's Best Novels Khaled Hosseini's "A Thousand Splendid Suns" is a genuine instant literary classic, and one destined to be remembered as one of 2007's best novels. It should be compared favorably to such legendary Russian novels like "War and Peace" and "Doctor Zhivago".